Propuesta de mejora del proceso de gestión del talento humano en el área de impresión flexográfica de cajas de cartón corrugado en Trupal S.A. - Martos Robles, Jean Carlos Aparicio (2022)
The objective of this project is to demonstrate the technical and economic viability of the implementation of a career line in the area of Flexographic Printing of the business unit of Corrugated Box at Trupal, which allows to have motivated and trained workers, maintaining the talent flow in the company; ensuring compliance with the productivity objective of the Operational Excellence project. The project raises the existence of a problem at Dong Fang 9 and 13 Flexographic Printer Machine, which did not reach the 30% productivity improvement target, associated with a low Global Equipment Effectiveness index (OEE, hereinafter, for its acronym in English), which is affected by the rates of availability, performance and quality. Among the engineering tools, continuous improvement and among others used to develop the proposal are the Cause and Effect Diagram to classify the potential causes that do not allow the objective of productivity improvement to be achieved, according to a focus group carried out with the staff of production; Pareto chart to prioritize the causes that originate longer machine downtimes; the 5 whys analysis to determine the root cause of the hypotheses obtained in the Cause and Effect Diagram and propose action plans; Methodology of factors and points for evaluation of positions; the Kanban method and Multi-skills Matrix for the design of the career line; analysis of employee turnover rates; Gantt chart; and, finally, the determination of costs and benefits generated. Finally, it was determined that the project, in the time horizon of 2 years, is viable and a saving of S/ 50 834 228 will be obtained and a return on investment for training (ROI) of S/ 163 will be obtained; that is, for each S/ 1 invested in the implementation of the Career Line proposal, a benefit of S/ 163 is generated.